STAGES OF EMERGENCE AND FORMATION OF NEW TRENDS IN BALLROOM DANCING («FORMATION») - Naurazbayeva Zh.T. (Arts Academy)
The article examines the history of the development of the sports ballroom dance style "Formation" and proposes a specific concept for training dancers in this direction. The research was conducted using methods of observation and analysis, literature review, interviews, and experiments. The relevance and novelty of the study lie in the attempt to systematize the process of formation and development of sports ballroom dances based on Kazakhstani material. Presenting its own vision of the stages of dance development (1968–1978 as the initial period, 1978–1988 as the time of active implementation of the club system, the turn of the century as an era of interest in European and Latin American programs), the article evaluates the positive experience of forming a team by the "Bomond Empire" club in 2011 and notes the weak development of "Formation" in Kazakhstan. After analyzing the problematic issues hindering the promotion of this type of sports ballroom dance (lack of adult dancers, mismatch of skill levels to standards, and low motivation among coaches), the author presents a personallytested concept of the "Formation" program adapted for the "Juvenile" category (ages 9–11). The main principles of the concept, according to the author, are teamwork aimed at developing solidarity, confidence, and artistry, as well as a systematic approach to training.